Structure of North American mantle constrained by simultaneous inversion of multiple-frequency SH, SS, and Love waves - Tian, Y; Zhou, Y; Sigloch, K; Nolet, G; Laske, G (2011)
We simultaneously invert for the velocity and attenuation structure of the North American mantle from a mixed data set: SH wave traveltime and amplitude anomalies, SS wave differential traveltime anomalies, and Love wave fundamental mode phase delays. All data are measured for multiple frequency bands, and finite frequency sensitivity kernels are used to explain the observations. In the resulting SH velocity model, a lower mantle plume is observed to originate at about 1500 km depth beneath the Yellowstone area, tilting about 40° from vertical. The plume rises up through a gap in the subducting Farallon slab. The SH velocity model confirms high-level segmentation of the Farallon slab, which was observed in the recent P velocity model. Attenuation structure is resolvable in the upper mantle and transition zone; in estimating it, we correct for focusing. High-correlation coefficients between δlnVS and δlnQS under the central and eastern United States suggest one main physical source, most likely temperature. The smaller correlation coefficients and larger slopes of the δlnQS - δlnV S relationship under the western United States suggest an influence of nonthermal factors such as the existence of water and partial melt. Finally, we analyze the influence of the different components of our data set. The addition of Love wave phase delays helps to improve the resolution of both velocity and attenuation, and the effect is noticeable even in the lower mantle. Copyright © 2011 by the American Geophysical Union.